2022
DOI: 10.1183/20734735.0010-2022
|View full text |Cite
|
Sign up to set email alerts
|

Industry influence in healthcare harms patients: myth or maxim?

Abstract: Healthcare is a major global industry accounting for a significant proportion of government spending. Drug and medical device manufacturers are publicly traded companies with a responsibility to their shareholders to maximise profits by increasing sales. In order to achieve this, industry exerts influence over every part of healthcare including academic research, medical education, clinical guideline development, physician prescribing and through direct interactions with patients. In contrast, healthcare servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 78 publications
1
6
0
Order By: Relevance
“…The same problem can be found in Greece too, where there is no consistency in what is announced on the pages of donors, recipients and SFEE's database. A similar picture is presented in the international bibliography, reflecting the current situation in Europe, with the need for a central regulatory authority being imperative (Trayer et al, 2022).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…The same problem can be found in Greece too, where there is no consistency in what is announced on the pages of donors, recipients and SFEE's database. A similar picture is presented in the international bibliography, reflecting the current situation in Europe, with the need for a central regulatory authority being imperative (Trayer et al, 2022).…”
Section: Discussionsupporting
confidence: 53%
“…This registry should be publicly available, easily accessible and all donations should be registered in a timely manner, allowing the scientific community, the authorities and the public in general to see where the funding is going and how it is being used. The funding of these groups should continue and be supported under conditions of control and transparency, to ensure that their actions are not commercialized (Sidiropoulos, 2023;Trayer et al, 2022).…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Such associations are common across modern health care, but the central role of implants and instrumentation in many contemporary spinal operations heightens the risk of industry influence 79 . Furthermore, while financial association alone does not prove that an individual surgeon's practice has been unduly altered, the impact of financial support on guideline formation, clinical decision making, and prescribing is well documented in other areas of medicine 80‐82 . A review of articles published from 2002 to 2003 found that 15.9% reported industry funding (57.9% of articles did not disclose a funding source) 83 .…”
Section: Industry Influencementioning
confidence: 99%
“… 79 Furthermore, while financial association alone does not prove that an individual surgeon's practice has been unduly altered, the impact of financial support on guideline formation, clinical decision making, and prescribing is well documented in other areas of medicine. 80 , 81 , 82 A review of articles published from 2002 to 2003 found that 15.9% reported industry funding (57.9% of articles did not disclose a funding source). 83 The same study noted industry‐funded trials were 3.3 times more likely to report a positive outcome compared with other trials ( P < 0.001).…”
Section: Industry Influencementioning
confidence: 99%
“…It is well established that medical drug and device industries can affect national research agendas through subtle influences at various levels across the healthcare marketplace [1][2][3]. These include evidence base production, evidence synthesis, understanding of harms issues, cost-effectiveness evaluation, clinical guidelines formation, healthcare professional education and direct influences on healthcare professional decisions [3].…”
Section: Introductionmentioning
confidence: 99%